A phase 3 double-blind randomized (CONSORT-compliant) study of azilsartan medoxomil compared to valsartan in Chinese patients with essential hypertension. Issue 32 (7th August 2020) - Wu, Jiahui; Du, Xin; Lv, Qiang; Li, Zhanquan; Zheng, Zeqi; Xia, Yong; Tang, Chengchun; Yao, Zhuhua; Zhang, Jun; Long, Mingzhi; Hisada, Michie; Wu, Jingtao; et al.
Abstract: Background: Azilsartan medoxomil (AZL-M), an angiotensin II receptor blocker, has a well-characterized efficacy and safety profile in patients with hypertension. AZL-M is approved for use in over 40 countries globally; however, it is not yet approved in China. Therefore, a phase 3 registration study to assess the efficacy (antihypertensive effect), safety, and tolerability of AZL-M compared with valsartan in Chinese patients with essential hypertension was undertaken. Methods: This multicenter, double-blind, randomized, 8-week phase 3 study compared AZL-M with valsartan in Chinese patients aged ≥18 years with essential hypertension. Endpoints included change from baseline to week 8 in trough sitting clinic systolic blood pressure (scSBP) and ambulatory blood pressure monitoring parameters. Results: Overall, 612 patients (mean age, 57.1 years; 57.5% male) were randomized to AZL-M 80 mg (n = 209), AZL-M 40 mg (n = 199), or valsartan 160 mg (n = 204). Baseline mean scSBP was similar in all groups (157.9–158.5 mm Hg). The mean reduction in trough scSBP from baseline to week 8 was significantly greater with AZL-M 80 mg than with valsartan (−24.2 vs −20.6 mm Hg; P = .010), and noninferior with AZL-M 40 mg versus valsartan (−22.5 vs −20.6 mm Hg; P = .184). Mean reduction in 24-hour mean systolic blood pressure (n = 257) was significantly greater with both AZL-M 80 mg (−17.0 mm Hg; P < .001) and AZL-M 40 mg (−14.7 mm Hg; P = .014) than with valsartan (−9.4 mm Hg). Treatment-emergent adverse events had similar incidence (52.8%–56.5%) across the treatment groups and were generally mild or moderate. Dizziness was the most frequent treatment-related treatment-emergent adverse events (AZL-M 80 mg, 1.9%; AZL-M 40 mg, 1.5%; valsartan, 1.0%). The safety and tolerability of AZL-M were comparable with valsartan. Conclusions: AZL-M was noninferior to valsartan at the 40-mg dose and superior to valsartan at the 80-mg dose in reducing trough scSBP, and showed acceptable safety—consistent with the AZL-M safety profile in other populations—in Chinese adults with hypertension. Trial Registration number: NCT02480764 Abstract : Supplemental Digital Content is available in the text